Smart-band BPM and Temperature Based on Android Using Wi-Fi Communication - Pandu Arsy Filonanda; I DEWA GEDE HARI WISANA; PRIYAMBADA CAHYA NUGRAHA (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2021)
Monitoring of patients is an integral part of health-care system, both in the hospital and at home. Monitoring devices are useful to monitor a person's health. Monitoring is necessary in case of symptoms of a disease that must be acted quickly to prevent the patient's condition from worsening. One way of monitoring patients' specifications is shown by their BPM value and temperature. The purpose of this study is the design of devices on a patient's wrist that can monitor BPM and his body temperature in real time and are not affected by distance. This research contribution is a system that can provide bradycardia indicators and tachycardia for BPM while hyperthermia and hypothermia for temperature. For a monitoring device to be more practical and efficient for use, it has a device with real time monitoring and a small frame of bracelets and alerts phones and emails during abnormal conditions. The design of the device uses the SEN0203 sensors as a BPM sensor that has analog and digital outputs, as well as MLX90614 sensors that have a digital output, and then data will be processed and shown live to oled ESP333TTGO and data sent to the blynk application on the phone aided by ESP32TTGO as a wifi module. The BPM has the smallest 0.1% error and the largest of 1.09% whereas the temperature has the smallest 0.19% and the largest of 1.63%. These results can be redeveloped on monitor patients to increase the efficiency of the remote monitoring system with alert conditions of patients at an abnormal time via mobile phones and emails.